Effects of acoustic environment on design work performance based on multitask visual cognitive performance in office space. (November 2021) - Meng, Qi; An, Yuying; Yang, Da
Abstract: The acoustic environment in the office space is a significant factor affecting workers' performance. Whereas existing research focuses mainly on the impact of the acoustic environment on single visual cognitive work performance, this study considers multitask visual cognitive work. Forty-one respondents were selected to participate in the multitask visual cognitive–behavioural cognitive experiment under different acoustic environments. The effects of different typical sound source types, sound pressure levels, and reverberation times on the performance of multitask visual cognition in design offices were examined. The results revealed the following. First, the sound source types have a significant impact on the reaction time of participants' work performance. Compared to the ambient environment (mean = 2.838 s), the reaction time performance is shortest under music sound (mean = 2.560 s). Second, the increase in traffic noise and air-conditioning noise will significantly reduce the memory accuracy of the location. For instance, when the traffic noise increases from 50 dBA to 65 dBA, the memory accuracy of the location is reduced by 4.42%. Third, the increase in the reverberation of speech will effectively shorten the reaction time and increase the memory accuracy of graphics. As the reverberation time of speech increases from 0.3 s to 1.5 s, the reaction time is reduced by 0.274 s. Meanwhile, 2.03% of the memory accuracy of graphics increased. Furthermore, the personal characteristics of the participants also affected visual cognitive work. Therefore, it is expected to improve the visual cognitive work performance of employees for room acoustic design. Graphical abstract: Image 1 Highlights: Acoustic environment affects office workers' speed, accuracy, memory performance. A multitask visual cognitive test for designers is used, rather than single-task. Surprisingly, natural sounds tend to reduce work performance. Loudness of sounds like traffic and ventilation should be optimally controlled. Gender, personality, and habits affect performance response to sound significantly.